HUBUNGAN KECEPATAN LARI ZIG-ZAG DENGAN KEMAMPUAN MENGGIRING BOLA PADA PERMAINAN SEPAK BOLA - Badaruddin, Badaruddin (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to determine the relationship between zigzag running speed and ball dribbling ability in soccer games. This research was conducted at SMA Negeri 2 Tomia, Wakatobi Regency, Southeast Sulawesi using a survey method. The instrument used to determine the independent variable was a zig-zag running speed test using a slalom test with the running speed changing direction over a pile, while to determine the dependent variable a ball dribbling test over obstacles was used. The research data was analyzed using product moment correlation statistics with a significance level of 0.05. The results of the research show that there is a positive relationship between zig-zag running speed and dribbling ability in soccer games, where Rxy = 0.62 > F table (0.5:40) = 0.304